Association of Radial Artery Access with Reduced Incidence of Acute Kidney Injury - Imad Uddin, Muhammad Ishaq Khan, Nabil Younas, Muhammad Omer Hashmi, Shireen Shah, Ayesha Mehmood (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Acute kidney injury (AKI) is a common complication that can occur after invasive cardiac procedures. This condition can cause significant morbidity and mortality, especially in high-risk patients, such as those with preexisting renal dysfunction. Objectives: The main objective of the study is to find the association of radial artery access with reduced incidence of acute kidney injury. Material and methods: The study is conducted at the Department of Cardiology, Hayatabad Medical Complex, Peshawar. This is a tertiary care center that provides cardiac care services to a large population of the Khyber Pakhtunkhwa province of Pakistan. The center has state-of-the-art facilities and a team of experienced cardiologists and cardiac surgeons who perform a variety of cardiac procedures, including PCI and CABG. Results: Based on a study of 300 patients undergoing cardiac catheterization, there was a significant association between the use of radial artery access and reduced incidence of acute kidney injury (AKI). The study found that 20% of patients who underwent femoral artery access developed AKI, compared to only 10% of patients who underwent radial artery access. This indicates that radial artery access may be a safer option for cardiac catheterization procedures, as it may help reduce the risk of AKI in patients. Conclusion: In conclusion, the present study provides evidence that radial artery access is associated with a lower incidence of acute kidney injury (AKI) in patients undergoing percutaneous coronary intervention (PCI).